1Q12 Loci Movement in the Interphase Nucleus Under the Action of ROS Is an Important Component of the Mechanism That Determines Copy Number Variation of Satellite III (1q12) in Health and Schizophrenia - Konkova, Marina Sergeevna; Ershova, Elizaveta Sergeevna; Savinova, Ekaterina Alekseevna; Malinovskaya, Elena Mikhailovna; Shmarina, Galina Vasilievna; Martynov, Andrey Vladimirovich; Veiko, Roman Vladimirovich; Zakharova, Nataly Vyacheslavovna; Umriukhin, Pavel; Kostyuk, Georgy Petrovich; Izhevskaya, Vera Leonidovna; Kutsev, Sergey Ivanovich; et al. (Frontiers in Cell and Developmental Biology, 2020)
Introduction. Genome repeat cluster sizes can affect the chromatin spatial configuration and function. Low-dose ionizing radiation (IR) induces an adaptive response (AR) in human cells. AR includes the change in chromatin spatial configuration that is necessary to change the expression profile of the genome in response to stress. The 1q12 heterochromatin loci movement from the periphery to the center of the nucleus is a marker of the chromatin configuration change. We hypothesized that a large 1q12 domain could affect chromatin movement, thereby inhibiting the AR. Materials and Methods. 2D FISH method was used for the satellite III fragment from the 1q12 region (f-SatIII) localization analysis in the interphase nuclei of healthy control lymphocytes (HC), schizophrenia patients (SZ) and in cultured mesenchymal stem cells (MSCs). The localization of the nucleolus was analyzed by the nucleolus Ag-staining. The non-radioactive quantitative hybridization technique (NQH) was used for the f-SatIII fragment content in DNA analysis. Satellite III fragments transcription was analyzed by RT-qPCR. Results. Low-dose IR induce the small-area 1q12 domains movement from the periphery to the central regions of the nucleus in HC lymphocytes and MSCs. Simultaneously, nucleolus moves from the nucleus center towards the nuclear envelope. The nucleolus in that period increases. The distance between the 1q12 domain and the nucleolus in irradiated cells is significantly reduced. The large-area 1q12 domains do not move in response to stress. During prolonged cultivation the irradiated cells with a large f-SatIII amount die and the population is enriched with the cells with low f-SatIII content. IR induces satellite III transcription in HC lymphocytes. Intact SZ patients’ lymphocytes have the same signs of nuclei activation as irradiated HC cells. Conclusion. When a cell population responds to stress, cells are selected according to the size of the 1q12 domain (the f-SatIII content). The low content of the f-SatIII repeat in SZ patients may be a consequence of the chronic oxidative stress and of a large copies number of the ribosomal repeats.